Narir Lekhani, Narittya Abong Bangladesher Galpo (নারীর লেখনী, নারীত্ব এবং বাংলাদেশের গল্প) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
From an anthropological perspective, feminism never disenfranchises men. Rather, how the 'Oppressed' women, 'Abla' women are becoming equal to men is the relevant issue. Traversbing a long time from Begum Rokeya, some traces of the power that the women writers of Bangladesh have achieved today have been discussed in this article. On International Women's Day on March 8, 1992, a bold slogan was seen on the streets of Dhaka in numerous festoons—'My body is mine, other have nothing to say.' The shocking slogan is actually of strong confidence, self-assurance and that women have their own rights of both mind and body. It is a big shock to the male dominated society. Rokeya showed the duplicity of patriarchy. Jahanara Imam shows how women can use their bodies to take revenge against Pakistani Razakars. Neelima Ibrahim's ‘Ramana Parke’ story shows male hypocritical love. Both Laila Samad's ‘Amurta Akanksha’ and Razia Mahbub's ‘Nirruttar’ stories capture the distorted form of female youthful desire. Motijan's girls with Selina Hossain have stormed Bengali literature. Taslima's ‘Matrittwa’ story also satirizes the male-imposed solution of denying women their own needs. Razia Khan's ‘Joy Jayanti’ highlights the difference between women captive in their homes and working women. ‘Ekti Idur O Koyekti Swarnamudra’ tells the story of a simple woman turning violent in her quest to survive. ‘Sarojinir Chobi’ is actually a slap against the social norms imposed by patriarchy. The shame is not Sarojini’s in this story. It is the society’s. Specifically, feminism is not seen in the stories as such. But women wanted to express their stand for their own issues, standing up against the authority of men.
Keywords: নারীত্ব; বাংলাদেশ; পুরুষতন্ত্র; মানবীবিদ্যাচর্চা; আন্দোলন; বুদ্ধিবৃত্তি; প্রতীক